Clinical care in the "Hot Zone". Issue 2 (22nd January 2008) - Byers, M; Russell, M; Lockey, D J
Abstract : The threat of chemical, biological, radiological and nuclear incidents is unlikely to decrease and preparations to deal with this type of incident are well established in most European emergency medical systems. In the UK medical care is not currently provided in the "Hot" or contaminated zone. This article discusses the background to the current threat and suggests that, where survivors are present in the "Hot Zone", medical care should be started there to minimise delay and maximise the chances of survival.